Thirty Years in Silicon Photonics: A Personal View - Pavesi, Lorenzo (Frontiers in Physics, 2021)
Silicon Photonics, the technology where optical devices are fabricated by the mainstream microelectronic processing technology, was proposed almost thirty years ago. I joined this research field at its start. Initially, I concentrated on the main issue of the lack of a silicon laser. Room temperature visible emission from porous silicon, first and from silicon nanocrystals, then, showed that optical gain is possible in low dimensional silicon but it is severely counterbalanced by nonlinear losses due to free carriers. Then, most of my research focus was on systems where photons show novel features such as Zener tunneling or Anderson localization. Here, the game was to engineer suitable dielectric environments (eg. one-dimensional photonic crystals or waveguide-based microring resonators) to control photon propagation. Applications of low dimensional silicon raised up in sensing (eg. gas-sensing or bio-sensing) and photovoltaics. Interestingly, microring resonators emerged as the fundamental device for integrated photonic circuit since they allow studying the hermitian and non-hermitian physics of light propagation as well as to demonstrate on-chip heavily integrated optical networks for reconfigurable switching application or neural networks for optical signal processing. Finally, I witnessed the emergence of quantum photonic devices, where linear and nonlinear optical effects generate quantum states of light. Here, quantum random number generators or heralded single photon sources are enabled by silicon photonics. All these developments are discussed in this review by following my own research path.